2004
DOI: 10.1093/auk/121.4.1146
|View full text |Cite
|
Sign up to set email alerts
|

Postfledging Movements and Survival of Juvenile Eastern Meadowlarks (Sturnella Magna) in Illinois

Abstract: Abstract The postfledging period is the least-studied stage of avian life cycles. Survival during this period has crucial effects on population dynamics. Survival of fledged young may be influenced by dispersal from their nest sites, because juveniles must cope with the hazards of novel environments. To better understand this important life stage, we used radiotelemetry techniques to study postfledging movements and survival of 50 juvenile Eastern Meadowlarks (St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 35 publications
6
54
2
Order By: Relevance
“…Predation is generally the primary cause of mortality during the post‐fledging period (Yackel Adams et al , Berkeley et al , Suedkamp Wells et al ), particularly within the first week for fledgling Grasshopper Sparrows (Hovick et al ). Because dependent birds are not foraging on their own, and are less able to escape predators because their flight feathers are not fully grown (Anders et al , Kershner et al , Suedkamp Wells et al , Hovick et al ), they may benefit from remaining in areas of greater vegetation cover. However, Jackrel and Reinart () found that snakes were more common in grassland areas with denser vegetation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Predation is generally the primary cause of mortality during the post‐fledging period (Yackel Adams et al , Berkeley et al , Suedkamp Wells et al ), particularly within the first week for fledgling Grasshopper Sparrows (Hovick et al ). Because dependent birds are not foraging on their own, and are less able to escape predators because their flight feathers are not fully grown (Anders et al , Kershner et al , Suedkamp Wells et al , Hovick et al ), they may benefit from remaining in areas of greater vegetation cover. However, Jackrel and Reinart () found that snakes were more common in grassland areas with denser vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…For the dependent‐age subset, one 6‐ to 8‐d‐old nestling from each nest ( N = 18) was selected at random for tracking. Only one nestling was tracked per nest to ensure independence of marked individuals (Kershner et al , Berkeley et al , Hovick et al ). For the independent‐age subset, previously banded nestlings ≥ 32‐d‐old were selected for tracking.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many altricial bird species have an extended period of post‐fledging care, and this period is often longer in brood parasites than in host fledglings (Soler et al , ). Despite its long duration and the fact that this period of care is critical for juvenile survival, because predation at this stage is very frequent (Naef‐Daenzer, Widmer & Nuber, ; Kershner, Walk & Warner, ; Grüebler & Naef‐Daenzer, ), the fledging period both of brood parasites and of hosts has not been sufficiently studied. Available information on relationships between brood parasites and their hosts during this period is very scarce.…”
Section: Other Host Defences Against Brood Parasitesmentioning
confidence: 99%